Impact of Two Antibiotic Therapies on Clinical Outcome and Gut Microbiota Profile in Liver Transplant Paediatric Candidates Colonized by Carbapenem-Resistant Klebsiella pneumoniae CR-KP - Cardile, Sabrina; Del Chierico, Federica; Candusso, Manila; Reddel, Sofia; Bernaschi, Paola; Pietrobattista, Andrea; Spada, Marco; Torre, Giuliano; Putignani, Lorenza (Frontiers in Cellular and Infection Microbiology, 2021)
Colonization by multidrug-resistant (MDR) organisms in liver transplant (LT) candidates significantly affects the LT outcome. To date, consensus about patient management is lacking, including microbiological screening indications. This pilot study aimed to evaluate the impact of carbapenem-resistant Klebsiella pneumoniae (CR-KP) colonization in LT paediatric candidates to enable optimal prevention and therapeutic strategies that exploit both clinical and microbiological approaches. Seven paediatric patients colonized by CR-KP were evaluated before and until one-year post LT. At the time of the transplant, patients were stratified based on antibiotic (ATB) prophylaxis into two groups: ‘standard ATB’ (standard ATB prophylaxis), and ‘targeted ATB’ (MDR antibiogram-based ATB prophylaxis). Twenty-eight faecal samples were collected during follow-up and used for MDR screening and gut microbiota 16S rRNA-based profiling. Post-transplant hospitalization duration was comparable for both groups. With the exception of one patient, no serious infections and/or complications, nor deaths were recorded. A progressive MDR decontamination was registered. In the ‘standard ATB’ group, overall bacterial richness increased. Moreover, 6 months after LT, Lactobacillus and Bulleidia were increased and Enterobacteriaceae and Klebsiella spp. were reduced. In the ‘targeted ATB’ group Klebsiella spp., Ruminococcus gnavus, Erysipelotrichaceae, and Bifidobacterium spp. were increased 12 months after LT. In conclusion, both antibiotics prophylaxis do not affect nor LT outcomes or the risk of intestinal bacterial translocation. However, in the ‘standard ATB’ group, gut microbiota richness after LT was increased, with an increase of beneficial lactic acid- and short-chain fatty acids (SCFA)-producing bacteria and the reduction of harmful Enterobacteriaceae and Klebsiella spp. It could therefore be appropriate to administer standard prophylaxis, reserving the use of ATB-based molecules only in case of complications.